If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9 = x + 6 Reorder the terms: 9 + 6x = x + 6 Reorder the terms: 9 + 6x = 6 + x Solving 9 + 6x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + 6x + -1x = 6 + x + -1x Combine like terms: 6x + -1x = 5x 9 + 5x = 6 + x + -1x Combine like terms: x + -1x = 0 9 + 5x = 6 + 0 9 + 5x = 6 Add '-9' to each side of the equation. 9 + -9 + 5x = 6 + -9 Combine like terms: 9 + -9 = 0 0 + 5x = 6 + -9 5x = 6 + -9 Combine like terms: 6 + -9 = -3 5x = -3 Divide each side by '5'. x = -0.6 Simplifying x = -0.6
| 9p-12=8p | | x-50.5=-16.9 | | 9(1+4n)=-279 | | 4-11b=15 | | 1/z=12/10z-8 | | g-9/9=4/9 | | 3y-5d=5d-4 | | 13+3s=-47 | | 6r+27=30 | | (x-2)(3x-12)=0 | | k-8/2=12 | | 13/8m=1/2 | | -5/2*=34 | | -2m/3=-12 | | 5(x+20)=3x+180 | | 3a-8=-6+8 | | 22=6c | | 8(-2x-4)+13=-52 | | x^4+4x^3 -x^2 +16x-20=0 | | 3a+9=4a-1 | | x^3-2x^2+5x-2=0 | | X-2/5=3/x | | 7+0.6y=19 | | 8x=26-50 | | 2x+16=130 | | 89-2x=6x+8 | | 3x+5-9=9 | | 4.2x=-4(0.62-1.2) | | 9x+40=3x+4 | | d-7=524 | | t/7.5=4 | | t/7.5-4 |